Implementing and Improving the Character According to the Contents Contained in Al-Islam and Kemuhammadiyahan - Elihami Elihami; Nursubihana Nursubihana (JURNAL EDUKASI NONFORMAL, 2021)
The purpose of this paper is to discuss morality in Al-Islam and Muhammadiyah. Many of us see that the current generation has paid less attention to implementing noble character in daily interactions. Morals are human behavior in everyday life that has been attached to a person. Morals involve matters relating to good, bad, right, and wrong actions in the actions of a human being whose role models are sourced from the Qur'an and the Hadith of the Prophet Muhammad. At the same time, ethics are derived from a place's culture and customs that apply in a society. Morals are one of the three pillars of Islam, namely: faith, law, and morality. In this paper, the author discusses the notion of morality and al-Islam and kemuhammadiyahan, human relations with God, human relations with humans, human relations with the natural surroundings.